ALIRAN- ALIRAN FILSAFAT DALAM MATEMATIKA - Agung Prabowo (Universitas Jenderal Soedirman, 2009)
Mathematical philosophy doesn’t add a number of new mathematical theorems or teories, so mathematical phylosophy is not mathematics. Mathematical phylosophy is a reflection on mathematics. After having studied for a long time, one need to reflect the result of the study by reflecting it to mathematical phylosophy. This article discusses the mathematical phylosophy streams and their role and function, and describes formalism mathematical phylosophy specially.